How to more effectively lobby the legislative branch of government: report the extent of intellectual disability amongst a politician's constituents. (30th May 2014) - Waldman, H. Barry; Perlman, Steven P.
ABSTRACT The use of national numbers and percentages to describe the millions of people with intellectual disabilities is beyond the comprehension of most people. The challenge is to personalize these numbers if we are to bring increased attention to these individuals. Examples of Census Bureau report data for the States, Congressional Districts, Counties, and High School districts are suggested as a format to lobby legislators with the realities of the numbers of their constituents who are affected by intellectual disabilities.